OPTIMALISASI DNS RECURSIVE UNTUK MEMPERCEPAT PENCARIAN INFORMASI DI INTERNET (STUDI KASUS : PT. PARSAORAN GLOBAL DATATRANS) - Rian Hidayat; Reza Aldiansyah; Dewa Agung Laksono; Sutriyono (Shofanah Media Berkah, 2023)
In developing digital network and infrastructure solutions, PT. Global Datatrans Partners with HSPnet Branding have built a wide and reliable network, by utilizing Internet Protocol (IP) technology as the basis for sending data, voice and video. The company has expertise and experience in designing, implementing, and managing reliable, scalable, and secure networks. However, with increasing access to fast and efficient internet, PT. Global Datatrans market, experienced several problems, such as: limited performance of DNS Recursive, as well as a lack of features which made DNS monitoring difficult. Recursive DNS (Domain Name System) is an important component in internet infrastructure that functions to translate domain names into IP addresses that computers can understand. In this report, the author will explore ways to optimize DNS Recursive to increase speed.